2021
DOI: 10.1111/jpi.12711
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod integration in C3H rd1 mice

Abstract: In mammals, the suprachiasmatic nuclei (SCN) constitute the main circadian clock, receiving input from the retina which allows synchronization of endogenous biological rhythms with the daily light/dark cycle. Over the year, the SCN encodes photoperiodic variations through duration of melatonin secretion, with abundant nocturnal levels in winter and lower levels in summer. Thus, light information is critical to regulate seasonal reproduction in many species and is part of the central photoperiodic integration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…[24][25][26] The total of 240 mice, comprising both the CD and ABX groups, were randomly allocated to 10 distinct subgroups, each exposed to a specific LD cycle as outlined in Figure 1B 1D), in accordance with previously documented protocols. [19][20][21][22] Each individual mouse was housed in a separate cage within a temperature-and humidity-controlled warehouse, adhering to regulatory guidelines. LD cycles were carefully manipulated using a LED light strip emitting a brightness of 150-200 lx, and a temperature range of 4500-5000 K. In the LD12/12 condition, lights were activated at Zeitgeber time 0 (ZT0) and deactivated at ZT12 (ZT0 representing lights-on).…”
Section: Animals Diets Antibiotic Treatment and Ld Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26] The total of 240 mice, comprising both the CD and ABX groups, were randomly allocated to 10 distinct subgroups, each exposed to a specific LD cycle as outlined in Figure 1B 1D), in accordance with previously documented protocols. [19][20][21][22] Each individual mouse was housed in a separate cage within a temperature-and humidity-controlled warehouse, adhering to regulatory guidelines. LD cycles were carefully manipulated using a LED light strip emitting a brightness of 150-200 lx, and a temperature range of 4500-5000 K. In the LD12/12 condition, lights were activated at Zeitgeber time 0 (ZT0) and deactivated at ZT12 (ZT0 representing lights-on).…”
Section: Animals Diets Antibiotic Treatment and Ld Cyclesmentioning
confidence: 99%
“…4,18 Recent findings have further highlighted the profound effects of extreme LD cycle alterations, such as constant darkness (LD0/24) and constant light (LD24/0), on the daily oscillations of physiological functions and GM. [19][20][21] Moreover, minor LD cycle alterations, including short light (LD8/16) and long light (LD16/8), have been extensively studied as models of circadian disorder in jet lag or shift workers. 21,22 Hence, in our study, we selected these four irregular LD cycles, along with the normal LD cycle (LD12/12), to investigate their regulation of the homeostatic crosstalk among the GM, oscillation of hypothalamic and hepatic CCs, and immunity and metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, sleep and wake cycle abnormalities of shift workers increase food intake at night and reduce light exposure, which in turn triggers metabolic disorders due to inadaptability to circadian rhythms, leading to a significant increase in the incidence of obesity, diabetes, and coronary heart disease (12). It is reported that the intrinsically photosensitive retinal ganglion cells (ipRGCs) can sensitively respond to the changes in the external light cycle, which adjusts the SCN to receive the signal input from the retina to synchronize the circadian rhythm with the LD cycles (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…At present, many circadian clock genes have been identified in animals including period circadian clock 1/2/3 ( Per1/2/3 ), cryptochrome 1/2 ( Cry1/2 ), brain and muscle ARNT-like 1 ( Bmal1 ), and circadian locomotor output cycle kaput ( Clock ) [ 3 , 4 ]. A central circadian clock located in the suprachiasmatic nucleus (SCN) coordinates the oscillation of the peripheral circadian clock, while the intrinsically photosensitive retinal ganglion cells (ipRGCs) send light signals into SCN to guide the central clock to periodically oscillate and output rhythmic behaviors consistent with daily changes [ 5 ]. The circadian clock is produced by the transcriptional-translational feedback loops (TTFLs) of circadian genes [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%